Utilization of Phytochemical Content of Nipah Leaf Extract in the Coastal Area of Indonesia - Zakyani, Nova N; Susanti, R; Widiatningrum, Talitha (JURNAL BUDIDAYA PERTANIAN, 2023)
Nypa fruticans Wurmb or ‘nipa’ is a palm plant that includes mangrove commodities, found along the mouths of tropical and subtropical rivers. Nipah forests in Indonesia are spread on the coast of the islands of Sumatra, Kalimantan, Sulawesi, Maluku, and Papua. Coastal communities in Indonesia usually use nipah as an ingredient in traditional medicine, food coloring, to various handicrafts. The main phytochemical composition of nipah is polyphenols, phenolics, alkaloids, tannins, flavonoids, and saponins. Therefore, the knowledge and utilization of this nipah plant need to be sought and studied more deeply to optimize its utilization. This study aims to find out the utilization of the phytochemical composition of nipah leaf extract on the coast of Indonesia. The results of the literature study on the phytochemical content of nipa leaves and their use have the potential as traditional medicine, and can act as antioxidants, antidiabetics, antimicrobials (antifungals and antibacterials), anticancer, anti-inflammatory, and analgesic. In addition to medicine, nipah plants are also used as roofs, livestock pens, or huts in gardens, brooms, handicrafts, fishing gear, as food coloring, as a source of food and beverages, to renewable energy fuel sources.